Vancomycin intermediate and vancomycin resistant Staphylococcus aureus: an upcoming threat - Patel, Alpa S.; Bhabhor, Ullas H.; Mullan, Summaiya A. (International Journal of Research in Medical Sciences, 2025)
Background: Either community or hospital settings, Staphylococcus aureus is a significant pathogen that causes mild localized infections of the skin to potentially fatal systemic infections. The increasing evidence of reduced vancomycin susceptibility (RVS) and vancomycin resistance in clinical MRSA isolates is troubling. There aren’t many therapeutic options available for such isolates. We have identified the most current pattern of antimicrobial resistance and specifically evaluated Staphylococcus aureus’s susceptibility profile to vancomycin. vancomycin-intermediate Staphylococcus aureus and isolates of Staphylococcus aureus that are resistant to vancomycin. Methods: Non-duplicate, consecutive isolates of S. aureus obtained from January 2021 to June 2022 were subject to antimicrobial susceptibility testing using standard disk diffusion tests or epsilometer tests according to the clinical laboratory standards institute 2021 requirements. Results: The total of 315 S. aureus were isolated during study period. Swab and pus sample shows highest isolation followed by other sample types. A total of 202 (64.1%) isolates were MRSA, while 111 (35.2%) were Inducible clindamycin positive ( ICR Positive). Antibiotic resistance observed is, penicillin (303/315, 96.1%), Ofloxacin (266/315, 84.4%), levofloxacin (255/315, 80.9%), Azithromycin (190/315, 60.3%) followed by other class of antibiotic groups. In our study Vancomycin , Linezolid and Teicoplanin are 100% sensitive. Vancomycin resistance is not noted in any isolates but we have 7 Vancomycin intermate isolates. Conclusions: Gate keeping in advent use of antibiotic is paramount importance to control the antibiotic resistance. As well as continuous laboratory monitoring of various antibiotic resistance pattern is needed.